The Efectiveness Of Using Blackpink As A Celebrity Endorser In The Launch Of The #Oreoblackpink Product On The @Oreo_Indonesia Instagram Account - Elysia Vina Surentang (Communication Science Department - Petra Christian University, 2023)
Celebrity endorsers are individuals who are trusted by companies to represent a product. A promotion delivered by a popular source or celebrity will attract more attention. Blackpink is a girl group from South Korea which is popular all over the world. PT. Mondelēz Indonesia appointed Blackpink as a celebrity endorser in the launch of the Oreo x Blackpink collaboration product, using Instagram social media as the main tool for conveying messages to the audience. In order to examine the effectiveness of a celebrity endorser, the TEARS model can be used, namely: trustworthiness, expertise, attractiveness, respect, similarity. This research is a descriptive quantitative research using an online survey method. The sampling technique was purposive sampling in accordance with the specified criteria in selecting respondents who filled out the questionnaire. Based on the results of the research findings, it can be concluded that the use of Blackpink as a celebrity endorser in launching #OREOBLACKPINK on the Instagram account @oreo_indonesia is effective. The indicators that produce the highest scores are attractiveness and respect (self-esteem).